My sister the super model - "Stine, Megan" (HarperCollinsEntertainment, London, 2002 London, 2002)
Ashley's going to be a model - and she can't wait. So when 'Real Teen magazine comes to school to pick their model of the month, Ashley is shocked as they choose Mary-Kate instead of her.
Keywords: Twins-English Fiction